PSXI-32 Ensiling time effects on nitrogen fractions and effects of ensiling corn and sorghum grains rehydrated on intake, ruminal and intestinal starch digestibility. (7th December 2018) - Valadares, S; Silva, B; Pacheco, M; Menezes, A; Godoi, L; Alhadas, H; Fonseca, F; Paulino, P; Renno, L
Abstract: This study aimed to evaluate the ensiling time effects on grain nitrogen fractions and the effects of ensiling corn and sorghum grains rehydrated on ruminal, intestinal and total starch digestion. At the trial beginning, corn and sorghum samples were milled in a 3mm sieve, rehydrated until 35% moisture and ensiled in bag silo during 0, 7, 14, 28, 60, 90, 120, 180 and 360d with three repetitions per ensiling time. These samples were analyzed for dry matter, soluble nitrogen, insoluble nitrogen and non-protein nitrogen. To evaluate digestibility the grains were ensiled 60d before the experiment beginning. Five Nellore rumen-cannulated bulls, with 262 ± 18 kg average BW were used, following a 5 × 5 Latin square design with a 2 × 2 + 1 factorial arrangement. Five experimental diets were tested, where four were composed by 28.44% corn silage, 60.83% corn and sorghum grains rehydrated or dried and 10.73% protein and mineral supplement. The fifth diet was based in dry corn with 45:55 roughage:concentrate ratio. Each experimental period lasted 22d, with 14d adaptation, 5d of total feces collection and 3 days collection to obtain omasal flow using double marker system (iNDF and Co-EDTA as markers). Data were analyzed using MIXED-SAS. There was a reduction (P<0.05) by both factors. There was an interaction between grain type and ensiling time for all parameters evaluated (Table 1). Therefore, longer ensiling times are related with a reduction in insoluble protein fraction and the prolamins break can explain the higher starch intestinal digestibility of rehydrated and ensiled grains.